Carrier‐Free ATP‐Activated Nanoparticles for Combined Photodynamic Therapy and Chemotherapy under Near‐Infrared Light (Small 11/2023). Issue 11 (15th March 2023) - Su, Zehou; Xi, Dongmei; Chen, Yingchao; Wang, Ran; Zeng, Xiaolong; Xiong, Tao; Xia, Xiang; Rong, Xiang; Liu, Ting; Liu, Wenkai; Du, Jianjun; Fan, Jiangli; et al.
Abstract : Carrier‐Free ATP‐Activated Nanoparticles In article number 2205825, Wen Sun and co‐workers develop ingenious adenosine triphosphate (ATP)‐activated nanoparticles (CDNPs) that are directly self‐assembled from photosensitizer (Cy‐I) and amphiphilic Cd(II) complex (DPA‐Cd). In cancer cells, CDNPs are disintegrated by ATP to release Cy‐I for generating single oxygen under 808 nm light and DPA‐Cd concurrently for chemotherapy.